Refining modifier as well as preparation method and application thereof

By using α-Al, Al4(Sr,La) and Ti2Al20La's refinement agent, the problem of limited refinement effect in the prior art was solved, and the significant refinement of the morphology of α-Al and eutectic Si in the Al-Si-Mg alloy was achieved and the mechanical properties of the morphology of α-Al and eutectic Si were improved.

CN119663038APending Publication Date: 2025-03-21LANZHOU UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411886334.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing refinement deteriorating agents have limited effect in improving the mechanical properties of Al-Si-Mg alloys, and it is difficult to effectively refine the morphology of α-Al grains and eutectic Si.

Method used

A refined metamorphic agent with phase composition including α-Al, Al4 (Sr, La) and Ti2Al20La was prepared by melt reaction and casting processes to release more Sr atoms to improve the deterioration effect of eutectic Si, and the growth of eutectic Si was hindered by pinning of Ti2Al20La.

Benefits of technology

The distance between the α-Al grains and secondary dendrites in Al-Si-Mg alloy is significantly refined, and the ultimate tensile strength, yield strength, elongation and microhardness of the alloy are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005199419580000011
    Figure HDA0005199419580000011
  • Figure HDA0005199419580000012
    Figure HDA0005199419580000012
  • Figure HDA0005199419580000013
    Figure HDA0005199419580000013
Patent Text Reader

Abstract

The invention provides a refining modifier as well as a preparation method and application thereof, and belongs to the technical field of aluminum alloys. The phase composition of the refining modifier provided by the invention comprises alpha-Al, Al4 (Sr, La) and Ti2Al20La. Al4 (Sr, La) is an Al4Sr phase, part of Sr atoms are replaced by La atoms, and the phase can release more Sr atoms, so that the metamorphism effect of eutectic Si is improved; the Ti2Al20La is partially enriched on the surface of the eutectic Si to play a pinning role, so that the growth of the eutectic Si is hindered, and meanwhile, the refinement of the primary alpha-Al phase also leads to the obvious increase of the grain boundary, so that the growth of the eutectic Si is inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum alloys, and in particular relates to a refinement modifier and a preparation method and application thereof. Background Art

[0002] Al-Si-Mg alloy is widely used in aerospace, manufacturing high-performance automobiles and marine vessels due to its good casting performance, light weight and strong plasticity. Generally speaking, the mechanical properties of Al-Si-Mg alloy are closely related to the size of α-Al grains, casting defects and the size and morphology of eutectic Si particles. The microstructure is mainly composed of primary α-Al and eutectic Si. Under normal cooling conditions, α-Al in its structure is usually in the form of dendrites, and eutectic silicon is usually unevenly distributed in the matrix in the form of coarse needles and plates. These needle-shaped eutectic Si will cause stress concentration during the alloy stretching process, thus becoming the main site of crack initiation, resulting in a decrease in the mechanical properties of the alloy.

[0003] At present, refining modifiers are mainly used to improve the morphology of primary α-Al dendrites and eutectic Si, thereby improving the mechanical properties of the alloy. Existing refining modifiers mainly include Al-Ti-B-La, Al-Ti-C-Sr, Al-Ti-B-RE and other composite master alloys, but the refining effect is limited. Summary of the invention

[0004] The object of the present invention is to provide a refinement modifier and its preparation method and application. The refinement modifier provided by the present invention can significantly refine the α-Al grains and the secondary dendrite arm spacing (SDAS) in the Al-Si-Mg alloy, thereby improving the mechanical properties of the alloy.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a refinement modifier, the phase composition of which includes α-Al, Al4 (Sr, La) and Ti2Al 20 La.

[0007] Preferably, the chemical composition of the refining modifier includes, by mass percentage, 2.80-3.20% Ti, 4.25-4.45% La, 7.75-8.15% Sr, ≤0.20% Fe, ≤0.03% Mn, ≤0.50% Zn and the balance Al.

[0008] The present invention also provides a method for preparing the refinement modifier described in the above technical solution, comprising the following steps:

[0009] (1) mixing raw materials and performing melt reaction to obtain a melt;

[0010] (2) Casting the melt obtained in step (1) to obtain a refined modifier.

[0011] Preferably, the raw materials in step (1) include Al-Ti-La master alloy and Sr block.

[0012] Preferably, the temperature of the melt reaction in step (1) is 900-950° C., and the time of the melt reaction is 30-60 min.

[0013] Preferably, the melt reaction in step (1) is carried out under stirring conditions.

[0014] Preferably, the casting temperature in step (2) is 850-870°C.

[0015] The present invention also provides the use of the refining modifier described in the above technical solution or the refining modifier prepared by the preparation method described in the above technical solution in Al-Si-Mg alloy.

[0016] Preferably, the mass of the refining modifier is 0.1-0.5% of the mass of the Al-Si-Mg alloy.

[0017] Preferably, the application method comprises:

[0018] The modified alloy is obtained by mixing an Al-Si-Mg alloy melt and a refining modifier and then casting.

[0019] The present invention provides a refinement modifier, the phase composition of which includes α-Al, Al4 (Sr, La) and Ti2Al 20 La. The Al4 (Sr, La) of the present invention is that part of the Sr atoms in the Al4Sr phase are replaced by La atoms. This phase can release more Sr atoms, thereby improving the modification effect of eutectic Si; Ti2Al 20 La will be partially enriched on the surface of eutectic Si, playing a pinning role, thereby hindering the growth of eutectic Si. At the same time, the refinement of the primary α-Al phase will also lead to a significant increase in grain boundaries, thereby inhibiting the growth of eutectic Si. Experimental results show that after adding 0.2wt.% of the refinement modifier of the present invention, the ultimate tensile strength, yield strength, elongation and microhardness of the Al-7Si-0.3Mg alloy are increased from 165.96MPa, 69.89MPa, 5.07% and 62.5HV in the untreated state to 220.60MPa, 100.81MPa, 9.92% and 79.3HV, respectively, which are increased by 32.92%, 44.24%, 95.66% and 26.88%, respectively. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The process flow chart of preparing the refined modifier in Example 1;

[0021] Figure 2 It is a schematic diagram of the standard tensile specimen;

[0022] Figure 3 The XRD pattern of the refined modifier prepared in Example 1;

[0023] Figure 4 This is the SEM image of the refined modifier prepared in Example 1;

[0024] Figure 5 for Figure 4 Enlarged view of area 1 in the middle;

[0025] Figure 6 for Figure 5 Point scan spectrum of midpoint 1;

[0026] Figure 7 for Figure 5 Surface scanning distribution diagram of Al element in the graph;

[0027] Figure 8 for Figure 5 Surface scanning distribution diagram of Ti element in the sample;

[0028] Fig. 9 for Figure 5 Surface scanning distribution diagram of La element in the graph;

[0029] Fig.10 for Figure 5 Surface scanning distribution diagram of Sr element in the sample;

[0030] Fig.11 for Figure 4 Enlarged view of area 2;

[0031] Fig.12 for Fig.11 Point scan spectrum of midpoint 2;

[0032] Fig.13 for Fig.11 Surface scanning distribution diagram of Al element in the graph;

[0033] Fig.14 for Fig.11 Surface scanning distribution diagram of Ti element in the sample;

[0034] Fig.15 for Fig.11 Surface scanning distribution diagram of La element in the graph;

[0035] Fig.16 for Fig.11 Surface scanning distribution diagram of Sr element in the sample;

[0036] Fig.17This is a TEM image of the refined modifier prepared in Example 1;

[0037] Fig.18 for Fig.17 HRTEM magnified images in the box;

[0038] Fig.19 for Fig.17 TEM-EDS point scan of midpoint 1;

[0039] Fig. 20 for Fig.17 TEM-EDS surface scanning distribution diagram of Al element in the sample;

[0040] Fig.21 for Fig.17 TEM-EDS surface scanning distribution diagram of Ti element in the sample;

[0041] Fig. 22 for Fig.17 TEM-EDS surface scanning distribution diagram of La element;

[0042] Fig.23 for Fig.17 TEM-EDS surface scanning distribution diagram of Sr element;

[0043] Fig.24 for Fig.17 Middle edge ]Ti2Al 20 SAED pattern of La phase;

[0044] Fig.25 for Fig.17 TEM-EDS line scan result diagram in the middle;

[0045] Fig.26 This is a bright field image of the Al4(Sr, La) phase in the refined modifier prepared in Example 1;

[0046] Fig. 27 Al4(Sr, La) phase[1 ] Selected area electron diffraction image of the crystal zone axis;

[0047] Fig.28 for Fig.26 High-resolution transmission electron microscopy images of

[0048] Fig.29 for Fig.26 TEM-EDS point scan of midpoint 1;

[0049] Fig.30 This is the selected area electron diffraction image of the Al4(Sr, La) phase along the

[110] crystal zone axis;

[0050] Fig.31 for Fig.26 High-resolution transmission electron microscopy images of

[0051] Fig.32 For comparison of the macrostructure of the Al-7Si-0.3Mg alloy in Application Example 1;

[0052] Fig.33 This is the EBSD image of the Al-7Si-0.3Mg alloy in comparative application example 1;

[0053] Fig.34 This is the grain size distribution diagram of the Al-7Si-0.3Mg alloy in comparative application example 1;

[0054] Fig.35 The macrostructure of the Al-7Si-0.3Mg alloy after refinement and modification in Application Example 1;

[0055] Fig.36 This is the EBSD image of the Al-7Si-0.3Mg alloy after refinement and modification in Application Example 1;

[0056] Fig.37 This is the grain size distribution diagram of the Al-7Si-0.3Mg alloy after refinement and modification in Application Example 1;

[0057] Fig.38 To compare the macrostructure of the Al-7Si-0.3Mg alloy after refinement and modification in Application Example 2;

[0058] Fig.39 This is the EBSD image of the Al-7Si-0.3Mg alloy after refinement and modification in comparative application example 2;

[0059] Fig.40 This is the grain size distribution diagram of the Al-7Si-0.3Mg alloy after refinement and modification in comparative application example 2;

[0060] Fig.41 The microstructure diagram of the Al-7Si-0.3Mg alloy in comparative application example 1;

[0061] Fig.42 The microstructure of the Al-7Si-0.3Mg alloy subjected to refinement and modification in Application Example 1;

[0062] Fig.43 The microstructure of the refined and modified Al-7Si-0.3Mg alloy in comparative application example 2;

[0063] Fig.44 It is a statistical diagram of the secondary dendrite arm spacing of comparative application example 1, application example 1 and comparative application example 2;

[0064] Fig.45The eutectic Si SEM morphology of the Al-7Si-0.3Mg alloy in comparative application example 1;

[0065] Fig.46 This is the Si SEM morphology of the Al-7Si-0.3Mg alloy subjected to refinement and modification in Application Example 1;

[0066] Fig.47 This is the Si SEM morphology of the Al-7Si-0.3Mg alloy subjected to refinement and modification in comparative application example 2;

[0067] Fig.48 for Fig.45 A partial enlarged view of the middle area 1;

[0068] Fig.49 for Fig.46 A partial enlarged view of the middle area 2;

[0069] Fig.50 for Fig.47 A partial enlarged view of the middle area 3;

[0070] Fig.51 It is a statistical diagram of eutectic Si size of the alloys of comparative application examples 1 to 2 and application example 1;

[0071] Fig.52 It is a graph comparing the mechanical properties of the alloys of Application Examples 1 to 2 and Application Example 1;

[0072] Fig.53 This is a graph comparing the fiber hardness and Q value of the alloys of Application Examples 1 to 2 and Application Example 1;

[0073] Fig.54 This is the tensile fracture morphology of the alloy of comparative application example 1;

[0074] Fig.55 This is the tensile fracture morphology of the alloy in Application Example 1;

[0075] Fig.56 This is the tensile fracture morphology of the alloy of comparative application example 2;

[0076] Fig.57 DSC curves of Al-7Si-0.3Mg alloys of Application Example 1 and Comparative Application Example during the heating and cooling processes;

[0077] Fig.58 TEM image of eutectic Si in Al-7Si-0.3Mg alloy of comparative application example 1;

[0078] Fig.59 HRTEM image of eutectic Si in Al-7Si-0.3Mg alloy of comparative application example 1;

[0079] Fig.60 For the Al-7Si-0.3Mg alloy of comparative application example 1, 0] Selected area electron diffraction of eutectic Si on the crystal zone axis;

[0080] Fig.61 TEM image of eutectic Si in Al-7Si-0.3Mg alloy of Application Example 1;

[0081] Fig.62 HRTEM image of eutectic Si in Al-7Si-0.3Mg alloy of Application Example 1;

[0082] Fig.63 In the Al-7Si-0.3Mg alloy of Application Example 1, [0 1] Selected area electron diffraction of twinned Si on the crystal zone axis;

[0083] Fig.64 The Ti2Al in the Al-7Si-0.3Mg alloy of Application Example 1 20 TEM bright field image of La phase;

[0084] Fig.65 for Fig.64 TEM-EDS surface scan of midpoint 1;

[0085] Fig.66 for Fig.64 TEM-EDS point scanning spectrum of midpoint 1;

[0086] Fig.67 for Fig.64 In [ 00] Selected area electron diffraction pattern on the crystal zone axis. DETAILED DESCRIPTION

[0087] The present invention provides a refinement modifier, the phase composition of which includes α-Al, Al4 (Sr, La) and Ti2Al 20 La.

[0088] In the present invention, the α-Al is a matrix.

[0089] In the present invention, the Al4(Sr, La) is preferably a rod-shaped phase; the lattice parameters of the Al4(Sr, La) are preferably a=b=0.438nm, c=1.10nm. In the present invention, the Al4(Sr, La) is obtained by replacing some Sr atoms in the Al4Sr phase with La atoms. This phase can release more Sr atoms, thereby improving the modification effect of eutectic Si.

[0090] In the present invention, the Ti2Al 20 The crystal structure of La is preferably Fd m structure; the Ti2Al 20 The lattice constant of La is preferably a=b=c=1.4764nm. 20 La will be partially enriched on the surface of eutectic Si, playing a pinning role, thereby hindering the growth of eutectic Si. At the same time, the refinement effect will lead to a significant increase in the primary α-Al phase, thereby inhibiting the growth of eutectic Si and further improving the refinement effect.

[0091] In the present invention, the Ti2Al 20 The size of La is preferably 200 to 300 nm.

[0092] In the present invention, the chemical composition of the refining modifier preferably includes Ti2.80-3.20%, La4.25-4.45%, Sr7.75-8.15%, Fe≤0.20%, Mn≤0.03%, Zn≤0.50% and the balance Al, more preferably Ti3.0%, La4.35%, Sr8.0% and the balance Al.

[0093] The Al4(Sr, La) of the present invention is that part of the Sr atoms in the Al4Sr phase are replaced by La atoms, and this phase can release more Sr atoms, thereby improving the modification effect of eutectic Si; Ti2Al 20 La will be partially enriched on the surface of eutectic Si, playing a pinning role, thereby hindering the growth of eutectic Si. At the same time, the refinement of the primary α-Al phase will also lead to a significant increase in grain boundaries, thereby inhibiting the growth of eutectic Si.

[0094] The present invention also provides a method for preparing the refinement modifier described in the above technical solution, comprising the following steps:

[0095] (1) mixing raw materials and performing melt reaction to obtain a melt;

[0096] (2) Casting the melt obtained in step (1) to obtain a refined modifier.

[0097] The present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.

[0098] The present invention mixes raw materials and performs melt reaction to obtain a melt.

[0099] In the present invention, the raw materials preferably include Al-Ti-La master alloy and Sr block.

[0100] In the present invention, the preparation method of the Al-Ti-La master alloy preferably comprises the following steps:

[0101] 1) mixing Al powder and Ti powder to obtain mixed powder;

[0102] 2) pressing the mixed powder obtained in step 1) to obtain a prefabricated block;

[0103] 3) The prefabricated block obtained in step 2) is mixed with the La block, and melted to obtain an Al-Ti-La master alloy.

[0104] In the present invention, Al powder and Ti powder are preferably mixed to obtain a mixed powder.

[0105] In the present invention, the purity of the Al powder is preferably ≥99.0%; the particle size of the Al powder is preferably 80-100 μm.

[0106] In the present invention, the purity of the Ti powder is preferably ≥99.0%; the particle size of the Ti powder is preferably 45-65 μm.

[0107] The present invention has no particular limitation on the ratio of the Al powder to the Ti powder, and the ratio can be selected according to the composition of the refining modifier.

[0108] In the present invention, the Al powder and the Ti powder are preferably mixed by ball milling; the rotation speed of the ball milling is preferably 100-200 r / min, more preferably 150 r / min; the time of the ball milling is preferably 2-4 hours, more preferably 3 hours. The ball milling mixing of the present invention can make the raw materials mixed more uniformly.

[0109] After obtaining the mixed powder, the present invention preferably presses the mixed powder to obtain a prefabricated block.

[0110] The present invention has no particular limitation on the pressing operation, and operations familiar to those skilled in the art may be used.

[0111] After obtaining the prefabricated block, the present invention preferably mixes the prefabricated block with a La block and melts them to obtain an Al-Ti-La master alloy.

[0112] In the present invention, the purity of the La block is preferably greater than 99.5%. The present invention has no special limitation on the size of the La block, as long as the composition of the fine modifier meets the requirements.

[0113] The present invention has no particular limitation on the ratio of the prefabricated blocks to the La blocks, and the ratio can be selected according to the composition of the refinement modifier.

[0114] The present invention has no special limitation on the operation of mixing the prefabricated block and the La block, and the technical scheme for preparing the mixed material well known to those skilled in the art can be adopted.

[0115] In the present invention, the melting temperature is preferably 1100-1200°C, more preferably 1150°C; the melting is preferably carried out under stirring conditions. The present invention has no special restrictions on the stirring operation, and the operation well known to those skilled in the art can be adopted. The present invention has no special restrictions on the melting time, as long as the raw materials are mixed uniformly.

[0116] In the present invention, the purity of the Sr powder is preferably greater than 99.0%. The present invention has no special limitation on the size of the Sr block, as long as the composition of the fine modifier meets the requirements.

[0117] The present invention has no special limitation on the operation of mixing the Al-Ti-La master alloy melt and the Sr block, and the operation well known to those skilled in the art can be adopted.

[0118] In the present invention, the temperature of the melt reaction is preferably 900-950°C; the time of the melt reaction is preferably 30-60 min. As an embodiment, the temperature of the melt reaction can be 910-940°C, or 920-930°C; the time of the melt reaction can be 35-55 min, or 40-50 min.

[0119] In the present invention, the melt reaction is preferably carried out under stirring conditions. The present invention has no special limitation on the stirring operation, and the operation well known to those skilled in the art can be adopted.

[0120] After obtaining the melt, the present invention casts the melt to obtain a refined modifier.

[0121] In the present invention, the casting temperature is preferably 850-870° C. As an embodiment, the casting temperature may be 855-865° C., or 860° C.

[0122] After the casting is completed, the present invention preferably cools the product obtained by the casting to obtain a refined modifier.

[0123] In the present invention, the refinement modifier is preferably annular. The present invention has no particular limitation on the size of the refinement modifier, and any size known to those skilled in the art may be used.

[0124] As an implementation manner, the inner diameter of the thinning modifier may be 45 mm; the outer diameter of the thinning modifier may be 70 mm; and the height of the thinning modifier may be 70 mm.

[0125] The invention adopts a melt reaction method to prepare a refining modifier, which can significantly refine and modify the Al-Si-Mg alloy and improve its mechanical properties.

[0126] The present invention also provides the use of the refining modifier described in the above technical solution or the refining modifier prepared by the preparation method described in the above technical solution in Al-Si-Mg alloy.

[0127] In the present invention, the mass of the refining modifier is preferably 0.1-0.5% of the mass of the Al-Si-Mg alloy, more preferably 0.2-0.4%, and even more preferably 0.3%.

[0128] In the present invention, the application method preferably includes:

[0129] The modified alloy is obtained by mixing an Al-Si-Mg alloy melt and a refining modifier and then casting.

[0130] The present invention has no particular limitation on the composition of the Al-Si-Mg alloy, and any Al-Si-Mg alloy known to those skilled in the art may be used. As an embodiment, the Al-Si-Mg alloy may be Al-7Si-0.3Mg.

[0131] The present invention has no special limitation on the preparation of the Al-Si-Mg alloy melt, and any Al-Si-Mg alloy melt well known to those skilled in the art may be used.

[0132] In the present invention, the temperature of mixing the Al-Si-Mg alloy melt and the refining modifier is preferably 720-750°C; the mixing time is preferably 10-30 minutes. As an embodiment, the mixing temperature can be 730-740°C; the mixing time can be 15-25 minutes, and can also be 20 minutes.

[0133] In the present invention, the mixing is preferably carried out under stirring conditions. The present invention has no particular limitation on the stirring operation, and any operation well known to those skilled in the art may be used.

[0134] After the mixing is completed, the present invention preferably mixes the melt obtained by the mixing with hexachloroethane, and then performs degassing and slagging in sequence.

[0135] In the present invention, the mass of the hexachloroethane (C2Cl6) is preferably 0.8 to 1.2% of the mass of the Al-Si-Mg alloy, more preferably 0.9 to 1.1%, and even more preferably 1.0%.

[0136] The present invention has no special limitation on the operation of mixing the melt with hexachloroethane, and the technical scheme for preparing the mixed material well known to those skilled in the art can be adopted.

[0137] The present invention has no special limitation on the degassing and slagging operations, and operations well known to those skilled in the art may be adopted.

[0138] In the present invention, the casting mold is preferably a steel mold; the steel mold is preferably preheated before casting; and the preheating temperature is preferably 200-250°C.

[0139] As an implementation manner, the outer diameter of the steel mold may be 140 mm; the inner diameter of the steel mold may be 120 mm; and the height of the steel mold may be 210 mm.

[0140] In the present invention, the casting temperature is preferably 710-720°C.

[0141] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0142] Example 1

[0143] The phase composition of the refining modifier is α-Al, Al4(Sr, La) and Ti2Al 20 La;

[0144] The chemical composition of the refining modifier is Ti 3%, La 4.35%, Sr 8% and the balance Al in terms of mass percentage;

[0145] The preparation method of the refinement modifier comprises the following steps:

[0146] (1) ball milling Al powder with a purity of ≥99.0% and a particle size of 80 to 100 μm and Ti powder with a purity of ≥99.0% and a particle size of 45 to 65 μm at 150 r / min for 3 h to obtain a mixed powder;

[0147] (2) pressing the mixed powder obtained in step (1) to obtain a prefabricated block; the pressing pressure is 98 kN and the pressing speed is 2 mm / min;

[0148] (3) mixing the prefabricated block obtained in step (2) with a La block having a purity greater than 99.5%, and melting the mixture at 1150° C. for 4 minutes under stirring to obtain an Al-Ti-La master alloy;

[0149] (4) mixing the Al-Ti-La master alloy obtained in step (3) with a Sr block having a purity greater than 99.0%, and performing a melt reaction in a medium frequency induction melting furnace at 920° C. for 45 minutes to obtain a melt; wherein the melt reaction is performed under stirring conditions;

[0150] (5) The melt obtained in step (4) is cast into a ring-shaped steel mold at 870° C. and then cooled to obtain a refined modifier with an inner diameter of 45 mm, an outer diameter of 70 mm, and a height of 70 mm.

[0151] Example 1 The process flow chart for preparing the fine modifier is as follows Figure 1 shown.

[0152] Comparative Example 1

[0153] The refining modifiers are Al-5Ti-B and Al-10Sr, and the mass ratio of the two is 1:1.

[0154] Application Example 1

[0155] The refinement and modification method of Al-7Si-0.3Mg alloy is:

[0156] A graphite crucible filled with industrial pure Al (purity of 99.7%) and Al-20Si alloy was placed in a KSY-15-16A silicon carbon rod resistance furnace for heating and melting. When the melt temperature reached 710°C, a pre-weighed Mg block was added, stirred and kept warm for 10 minutes, then the temperature was raised to 740°C, 0.2wt.% of the refining modifier of Example 1 was added, stirred and kept warm for 15 minutes, and then 1.0% C2Cl6 was added for refining and degassing. The crucible was taken out and the slag was skimmed. When the melt in the crucible was cooled to 720°C, it was cast into a steel mold (inner diameter 120mm, outer diameter 140mm, height 210mm) preheated at 200°C to obtain the refined and modified Al-7Si-0.3Mg alloy, recorded as 2#.

[0157] Comparative application example 1

[0158] Al-7Si-0.3Mg alloy (not refined and modified) is marked as 1#.

[0159] Comparative Application Example 2

[0160] On the basis of Application Example 1, the refining modifier was changed to 0.4wt.% of the refining modifier of Comparative Example 1 (i.e., 0.2wt.% Al-5Ti-B + 0.2wt.% Al-10Sr), and other conditions remained unchanged, to obtain the refined and modified Al-7Si-0.3Mg alloy, which was recorded as 3#.

[0161] The chemical composition of Al-7Si-0.3Mg alloy is shown in Table 1.

[0162] Table 1 Chemical composition of Al-7Si-0.3Mg alloy

[0163] chemical composition Si Mg Fe Ti Mn Zn Al Content / wt% 6.982 0.315 0.110 0.382 0.014 0.176 margin

[0164] The phase characterization of the refined modifier prepared in Example 1 was carried out using a Bruker D8 X-ray diffractometer (XRD) with CuKα radiation, with a 2θ scanning range of 20° to 90° and a scanning rate of 4° / min.

[0165] The Al-7Si-0.3Mg alloy prepared in Example 1 and Comparative Application Examples 1 to 2 was ground and polished using sandpaper, and then electropolished for 12 seconds using an electrolyte (10 vol.% HClO4+90 vol.% C2H5OH) to obtain an alloy metallographic sample.

[0166] TescanMira4 (SEM) and FelTalos F200X (TEM) were used to analyze the microstructure of the alloy, and Zeiss Gemini 300 thermal field emission electron microscope with Oxford-SYMETRY S3 probe was used for EBSD analysis.

[0167] The microhardness of the samples was measured using a Wilson VH1102 microhardness tester. The secondary dendrite arm spacing (SDAS) of α-Al dendrites and the aspect ratio of eutectic Si were calculated using Image ProPlus software. The alloy samples were processed into standard tensile specimens according to GB / 228.1-2010, such as Figure 2 As shown, the mechanical properties test was carried out using an AG-10TA universal tensile testing machine with an extensometer, with a tensile rate of 0.2 mm / min, in units of mm.

[0168] Figure 3 The XRD pattern of the refined modifier prepared in Example 1; Figure 4 This is the SEM image of the refined modifier prepared in Example 1; Figure 5 for Figure 4 Enlarged view of area 1 in the middle; Figure 6 for Figure 5 Point scan spectrum of midpoint 1; Figure 7 for Figure 5 Surface scanning distribution diagram of Al element in the graph; Figure 8 for Figure 5 Surface scanning distribution diagram of Ti element in the sample; Fig. 9 for Figure 5 Surface scanning distribution diagram of La element in the graph; Fig.10 for Figure 5 Surface scanning distribution diagram of Sr element in the sample; Fig.11 for Figure 4 Enlarged view of area 2; Fig.12 for Fig.11 Point scan spectrum of midpoint 2; Fig.13 for Fig.11 Surface scanning distribution diagram of Al element in the graph; Fig.14 for Fig.11Surface scanning distribution diagram of Ti element in the sample; Fig.15 for Fig.11 Surface scanning distribution diagram of La element in the graph; Fig.16 for Fig.11 Surface scanning distribution diagram of Sr element in.

[0169] Figure 5 The point scan results of midpoint 1 and Fig.11 The point scanning results of midpoint 2 are shown in Table 2.

[0170] Table 2 Figure 5 The point scan results of midpoint 1 and Fig.11 Point scanning results of midpoint 2

[0171] composition Al(At.%) Ti(At.%) La(At.%) Sr (At.%) phase of matter Point 1 85.93 9.63 3.31 1.13 <![CDATA[Ti2Al 20 The]]> Point2 82.41 0.31 3.06 13.22 <![CDATA[Al4(Sr,La)]]>

[0172] from Figure 3 It can be seen that the main phase composition of the refining modifier is α-Al, Al4Sr and Ti2Al 20 La phase and a small amount of La phase.

[0173] from Figure 4 From the SEM morphology, it can be seen that both block-shaped and rod-shaped structures are distributed in the matrix.

[0174] according to Figure 7 The EDS surface scanning results are combined with the EDS point scanning results of Table 2, and it is determined that the bulk phase is Ti2Al 20 La Xiang.

[0175] Depend on Fig.13 It can be seen that the aggregation of Al, Sr and La elements in the rod-shaped phase is significant. Combined with the point 2 EDS scanning results in Table 2, it can be seen that the atomic ratio of Al:Sr:La is about 26.93:4.32:1, that is, the atomic content of Al is about 4 times the sum of Sr and La atoms, so it is inferred that the rod-shaped phase is Al4 (Sr, La) phase.

[0176] In order to study the Ti2Al 20 The structural characteristics of the La phase were analyzed by TEM. Fig.17 This is a TEM image of the refined modifier prepared in Example 1; Fig.18 for Fig.17 HRTEM magnified images in the box; Fig.19 for Fig.17 TEM-EDS point scan of midpoint 1; Fig. 20 for Fig.17 TEM-EDS surface scanning distribution diagram of Al element in the sample; Fig.21 for Fig.17 TEM-EDS surface scanning distribution diagram of Ti element in the sample; Fig. 22for Fig.17 TEM-EDS surface scanning distribution diagram of La element; Fig.23 for Fig.17 TEM-EDS surface scanning distribution diagram of Sr element; Fig.24 for Fig.17 Middle edge ]Ti2Al 20 SAED pattern of La phase; Fig.25 for Fig.17 TEM-EDS line scan results.

[0177] pass Fig.24 Diffraction calibration, combined with Fig.19 and 20 TEM-EDS point scanning and surface scanning analysis confirmed that the phase is Ti2Al 20 La Xiang.

[0178] Calculated using Digital-Micrograph Fig.17 Ti2Al in the box area 20 The atomic layer spacing of La phase in this direction is 0.51nm. From the figure, we can see that α-Al and Ti2Al 20 There is a clear interface between the La phases. Fig.25 TEM-EDS line scan, illustrating α-Al and Ti2Al 20 There is no special coherence between La phases, which also proves that the Ti2Al 20 The La phase does not interact significantly with the α-Al matrix.

[0179] The Al4Sr phase in the refining modifier of the present invention forms the Al4(Sr, La) phase because part of the Sr atoms are replaced by La atoms. To further confirm that the rod-shaped phase is the Al4(Sr, La) phase, TEM analysis of the phase was performed. Figures 26 to 31 This is a TEM analysis diagram of the Al4 (Sr, La) phase in the refined modifier prepared in Example 1; wherein, Fig.26 This is a bright field image of the Al4(Sr, La) phase in the refined modifier prepared in Example 1; Fig. 27 Al4(Sr, La) phase[1 ] Selected area electron diffraction (SAED) image of the crystal zone axis; Fig.30 This is the selected area electron diffraction (SAED) image of the Al4 (Sr, La) phase along the

[110] crystal zone axis; Fig.28 and 31 Both Fig.26 High-resolution transmission electron microscopy (HRTEM) images of Fig.29 for Fig.26TEM-EDS point scan of midpoint 1.

[0180] from Figures 26 to 31 It can be seen that the atomic ratio of Al:(Sr+La) is about 4:1; Fig. 27 and 30 From the SAED graph, we can see that the crystal structure of Al4(Sr, La) phase belongs to the tetragonal system. Fig.28 and 31 It can be seen that the interplanar spacings of the (110) and (002) planes are 0.31 nm and 0.55 nm, respectively. Therefore, the lattice parameters of the Al4(Sr, La) phase can be calculated to be a=b=0.438 nm, c=1.10 nm, which are similar to the lattice parameters of the Al4Sr phase (a=b=0.446 nm, c=1.107 nm).

[0181] In addition, the morphology of the Al4Sr phase directly affects its modification effect. Compared with the needle-shaped Al4Sr phase, the Sr atoms in the rod-shaped Al4Sr phase are more easily freed from the phase, so that more free Sr atoms can be enriched on the growth step at the front of the eutectic Si interface, inducing the generation of more twins, thereby improving its modification effect. In the present invention, the Al4Sr phase morphology is changed to rod-shaped due to the replacement of some Sr atoms by La atoms, which can improve the modification effect on the aluminum alloy.

[0182] Study on the refining and modification effect of the refined modifier prepared in Example 1 on the Al-7Si-0.3Mg alloy:

[0183] Fig.32 For comparison of the macrostructure of the Al-7Si-0.3Mg alloy in Application Example 1; Fig.33 This is the EBSD image of the Al-7Si-0.3Mg alloy in comparative application example 1; Fig.34 This is the grain size distribution diagram of the Al-7Si-0.3Mg alloy in comparative application example 1; Fig.35 The macrostructure of the Al-7Si-0.3Mg alloy after refinement and modification in Application Example 1; Fig.36 This is the EBSD image of the Al-7Si-0.3Mg alloy after refinement and modification in Application Example 1; Fig.37 This is the grain size distribution diagram of the Al-7Si-0.3Mg alloy after refinement and modification in Application Example 1; Fig.38 To compare the macrostructure of the Al-7Si-0.3Mg alloy after refinement and modification in Application Example 2; Fig.39 This is the EBSD image of the Al-7Si-0.3Mg alloy after refinement and modification in comparative application example 2; Fig.40 This is the grain size distribution diagram of the Al-7Si-0.3Mg alloy after refinement and modification in comparative application example 2.

[0184] from Figures 32-34 It can be seen that the untreated Al-7Si-0.3Mg alloy has coarse grains in its macrostructure, with an average grain size of 440.18 μm.

[0185] from Figures 35-40 It can be seen that the grains in the macroscopic structure of the alloy treated with 0.2wt.% refining modifier are significantly smaller, and the average grain size is 148.47μm. Compared with the untreated alloy, the average α-Al grain size is reduced by 66.21%. Compared with the Al-7Si-0.3Mg alloy treated with the refining modifier of Example 1, the alloy treated with Comparative Example 1 (0.2wt.% Al-5Ti-B + 0.2wt.% Al-10Sr) has a poor refining effect, and the average α-Al grain size is only reduced to 279.06μm.

[0186] Fig.41 The microstructure diagram of the Al-7Si-0.3Mg alloy in comparative application example 1; Fig.42 The microstructure of the Al-7Si-0.3Mg alloy subjected to refinement and modification in Application Example 1; Fig.43 The microstructure of the refined and modified Al-7Si-0.3Mg alloy in comparative application example 2; Fig.44 It is a statistical diagram of the secondary dendrite arm spacing (SDAS) of comparative application example 1, application example 1 and comparative application example 2.

[0187] from Figures 41-44 It can be seen that the SDAS of the untreated alloy is as high as 27.78 μm, while the SDAS of the alloy treated with 0.2 wt.% refinement modifier of Example 1 is reduced to 12.72 μm, a decrease of 54.21%. The SDAS of the Al-7Si-0.3Mg alloy treated with (0.2 wt.% Al-5Ti-B + 0.2 wt.% Al-10Sr) is only reduced to 16.52 μm.

[0188] Fig.45 The eutectic Si SEM morphology of the Al-7Si-0.3Mg alloy in comparative application example 1; Fig.46 This is the Si SEM morphology of the Al-7Si-0.3Mg alloy subjected to refinement and modification in Application Example 1; Fig.47 This is the Si SEM morphology of the Al-7Si-0.3Mg alloy subjected to refinement and modification in comparative application example 2; Fig.48 for Fig.45 A partial enlarged view of the middle area 1; Fig.49 for Fig.46 A partial enlarged view of the middle area 2; Fig.50 for Fig.47 A partial enlarged view of the middle area 3; Fig.51This is a statistical diagram of the eutectic Si size of the alloys of Comparative Examples 1 to 2 and Application Example 1.

[0189] from Fig.45 It can be seen that the morphology of eutectic Si in the untreated alloy is plate-like and long needle-like, and is unevenly distributed in the matrix, with obvious aggregation.

[0190] from Fig.46 It can be seen that the morphology of eutectic Si in the alloy structure treated with the refinement modifier of the present invention changes from plate-like to fibrous and granular, and the segregation of eutectic Si is significantly weakened. Fig.51 From the size statistics of eutectic Si, the aspect ratio of eutectic Si is reduced from 2.94 to 2.04, and the roundness is improved.

[0191] from Fig.47 and 51 It can be seen that the morphology of eutectic Si in the alloy treated with (0.2wt.%Al-5Ti-B+0.2wt.%Al-10Sr) is mostly short rod and granular, and the aspect ratio of eutectic Si is reduced to 2.62, which is only reduced by 10.88%.

[0192] Fig.52 This is a diagram for comparing the mechanical properties of the alloys of Application Examples 1 to 2 and Application Example 1; Fig.53 This is a graph comparing the fiber hardness and Q value of application examples 1 to 2 and the alloy of application example 1.

[0193] from Figures 52-53 It can be seen that the ultimate tensile strength, yield strength, elongation and microhardness of the untreated Al-7Si-0.3Mg alloy are 165.96MPa, 69.89MPa, 5.07% and 62.5HV, respectively; when 0.2wt.% of the refining modifier of Example 1 is added, the ultimate tensile strength, yield strength, elongation and microhardness of the Al-7Si-0.3Mg alloy reach 220.60MPa, 100.81MPa, 9.92% and 79.3HV, respectively; compared with the untreated Al-7Si-0.3Mg alloy, the ultimate tensile strength, yield strength, elongation and microhardness of the alloy are increased by 32.92%, 44.24%, 95.66% and 26.88%, respectively, and are significantly better than the alloy treated with (0.2wt.%Al-5Ti-B+0.2wt.%Al-10Sr).

[0194] The present invention also introduces the Q value to measure the comprehensive mechanical properties of the alloy:

[0195] Q = UTS + a × log (E1) Formula I;

[0196] In Formula I, for hypoeutectic aluminum-silicon alloy, a=150 MPa.

[0197] from Fig.53 It can be seen that the Q value of the untreated Al-7Si-0.3Mg alloy is 271.71 MPa; the Q value of the alloy treated with 0.2wt.% of the refining modifier of Example 1 is as high as 370.60 MPa, and the Q value of the alloy treated with (0.2wt.% Al-5Ti-B+0.2wt.% Al-10Sr) is 333.49 MPa, which further proves that the refining modifier of the present invention can significantly improve the mechanical properties of the Al-7Si-0.3Mg alloy.

[0198] Fig.54 This is the tensile fracture morphology of the alloy of comparative application example 1; Fig.55 This is the tensile fracture morphology of the alloy in Application Example 1; Fig.56 This is the tensile fracture morphology of the alloy in comparative application example 2.

[0199] from Figures 54-55 It can be seen that the untreated alloy has a large number of dissociation platforms and fewer tearing edges on the fracture surface, which is a brittle fracture; when the alloy is treated with 0.2wt.% of the refining modifier of Example 1, the α-Al grains in the alloy structure are refined, the eutectic Si morphology is improved, and the crack propagation of the alloy is hindered by the fine grains during stretching, so that the crack propagates along the grain boundary, thereby forming an intergranular fracture, and its fracture characteristics are: a smaller dissociation platform, more tearing edges, and a small amount of dimples; while the alloy treated with (0.2wt.% Al-5Ti-B + 0.2wt.% Al-10Sr) has more tearing edges on the fracture surface, a smaller dissociation platform, and no dimples, but it is still a brittle fracture.

[0200] Analysis of the refinement and modification mechanism of the refinement and modification agent prepared in Example 1:

[0201] Fig.57 DSC curves of the Al-7Si-0.3Mg alloy of Application Example 1 and Comparative Application Example 1 during the heating and cooling processes.

[0202] from Fig.57 It can be seen that during the heating process of the alloy, two endothermic peaks appear between 550 and 625 °C, and a eutectic reaction occurs at Peak 1:

[0203] L→α-Al+Si Formula II;

[0204] The melting reaction of α-Al occurs at Peak 2. During the cooling process of the alloy, two exothermic peaks Peak 3 and Peak 4 also appear. Peak 3 represents the initial solidification of α-Al, and Peak 4 represents the initial nucleation of eutectic Si. The undercooling degree is obtained in the DSC curve using the Muller method, and the calculation method is as follows:

[0205] Δt=t M -t N Formula III;

[0206] In formula III, t M is the initial melting temperature, t N is the initial nucleation temperature of the eutectic reaction.

[0207] The calculation results are shown in Table 3.

[0208] Table 3 DSC quantitative analysis results of Al-7Si-0.3Mg alloy of Application Example 1 and Comparative Application Example 1

[0209] project <![CDATA[t M / ℃]]> <![CDATA[t N / ℃]]> Δt / ℃ Peak3 / ℃ Peak4 / ℃ Comparative application example 1 550.4 601.3 50.9 618.8 582.5 Application Example 1 549.8 605.3 55.4 627.5 587.9

[0210] As can be seen from Table 3, the initial nucleation temperatures of the alloys before and after refinement and modification are 601.3℃ and 605.3℃, respectively. Compared with the untreated alloy, the supercooling of the alloy treated with the refinement modifier increased by 4.5℃, indicating that the refinement modifier provides a greater driving force for the nucleation of the eutectic reaction. At the same time, it also promotes the nucleation of eutectic Si. This phenomenon provides strong evidence for α-Al grain refinement and eutectic Si modification.

[0211] Bramfitt proposed a nucleation theory that uses the lattice mismatch δ to evaluate whether a particle can become a heterogeneous nucleation point. Usually, when δ<6%, the nucleation rate is considered to be the highest; when 6%<δ<15%, the nucleation rate is considered to be medium; when δ>15%, the nucleation rate is considered to be invalid. A necessary condition for the second phase particles to become effective nucleation points of α-Al is that the crystal structure of the second phase particles is similar to that of α-Al. The smaller the difference in lattice constants, the stronger the ability to serve as heterogeneous nucleation points. According to Figures 3 to 16 The XRD phase analysis and energy spectrum characterization results show that Ti2Al 20 The crystal structure of La phase is structure, the lattice constant is a=b=c=1.4764nm. Similarly, the crystal structure of Al is Structure, lattice constant a=b=c=0.4041nm. Ti2Al 20 The crystal plane of La phase has a variety of matching relationships with the α-Al crystal plane, among which (001) Al / / (001) Ti2Al20La 、(111) Al / / (001) Ti2Al20La ,

[110] Al / /

[001] Ti2Al20La The mismatch δ of Ti2Al 20 There is an obvious orientation relationship between the La phase and the α-Al crystal plane family.20 The La phase has the conditions to become a heterogeneous nucleation point, so it can better refine the α-Al grains.

[0212] Fig.58 TEM image of eutectic Si in Al-7Si-0.3Mg alloy of comparative application example 1; Fig.59 HRTEM image of eutectic Si in Al-7Si-0.3Mg alloy of comparative application example 1; Fig.60 For the Al-7Si-0.3Mg alloy of comparative application example 1, 0] Selected area electron diffraction of eutectic Si on the crystal zone axis; Fig.61 TEM image of eutectic Si in Al-7Si-0.3Mg alloy of Application Example 1; Fig.62 HRTEM image of eutectic Si in Al-7Si-0.3Mg alloy of Application Example 1; Fig.63 In the Al-7Si-0.3Mg alloy of Application Example 1, [0 1] Selected area electron diffraction of twinned Si on the crystal zone axis.

[0213] from Fig.58 It can be seen that the surface of eutectic Si in the untreated alloy is smooth and has few twins. The sharp ends of eutectic Si will cause stress concentration when the alloy is subjected to external force, thereby reducing the mechanical properties of the alloy.

[0214] In the present invention, R Sr / R Si =1.72, which is close to the atomic radius ratio that induces twinning of eutectic Si. Therefore, Sr atoms can induce the formation of Si twins. Fig.61 ) The twin density on the eutectic Si surface increases, and the angle between the twins is 70.61° ( Fig.62 ).

[0215] from Fig.63 It can be seen that a large number of twins are formed on the surface of eutectic Si after refinement and modification, and the modification mechanism is consistent with the impurity-induced twinning (IIT) mechanism. The IIT mechanism believes that the prerequisite for the formation of twins must be that the atomic radius of the modified element and the atomic radius of the Si element R / R Si When =1.65, the metamorphic atoms enriched on the growth steps at the front edge of the Si interface will change the stacking position of the eutectic Si atomic layer, thereby changing the growth mode of Si and inducing twinning of the Si phase.

[0216] Fig.64 The Ti2Al in the Al-7Si-0.3Mg alloy of Application Example 1 20 TEM bright field image of La phase; Fig.65 for Fig.64 TEM-EDS surface scan of midpoint 1; Fig.66 for Fig.64 TEM-EDS point scanning spectrum of midpoint 1; Fig.67 for Fig.64 In [ 00] Selected area electron diffraction pattern on the crystal zone axis.

[0217] from Figures 64-67 It can be seen that the atomic ratio of Al, Ti, and La is about 20:2:1; Fig.67 It can be seen that the particles are Ti2Al 20 La particles, the size is about 200 ~ 300nm; compared with before adding Ti2Al 20 The size of La phase is significantly reduced, which indicates that the refining modifier has a great influence on the Ti2Al 20 The La phase was partially dissolved.

[0218] from Fig.64 It can be seen that some white particles Ti2Al 20 La is enriched on the surface of eutectic Si, which plays a pinning role, thereby hindering the growth of eutectic Si and refining the eutectic Si.

[0219] In summary, the modification effects of the refinement modifier of the present invention on eutectic Si are mainly as follows: (1) the formation of the new phase Al4 (Sr, La) enables the refinement modifier of the present invention to release more Sr atoms during the refinement and modification process, thereby improving the modification effect of eutectic Si; (2) part of Ti2Al 20 La particles are enriched on the surface of eutectic Si, which plays a pinning role, thereby hindering the growth of eutectic Si; (3) At the same time, the refinement of the primary α-Al phase will also lead to a significant increase in grain boundaries, thereby inhibiting the growth of eutectic Si. This is also the reason why the refinement modifier of the present invention has an excellent refinement and modification effect.

[0220] In summary, the main phase compositions of the refinement modifier of the present invention are α-Al, Al4(Sr, La) and Ti2Al 20 La phase; the refinement modifier of the present invention can significantly refine the α-Al grains and SDAS in the Al-7Si-0.3Mg alloy. The average grain sizes of SDAS and α-Al are reduced from 33.78 and 440.18 μm before treatment to 12.72 and 148.74 μm, respectively. The increase of melt undercooling and Ti2Al 20La phase can be used as heterogeneous nucleation point, which is the main reason for grain refinement. The refinement modifier of the present invention has an excellent modification effect on eutectic Si. Compared with the untreated alloy, after adding 0.2wt.% of the master alloy, the eutectic Si in the alloy changes from plate-like and long needle-like to fibrous and granular, and the aspect ratio decreases from 2.94 to 2.04. This is because the formation of the new phase Al4 (Sr, La) enables the refinement modifier of the present invention to release more Sr atoms and Ti2Al 20 The pinning effect of La phase hinders the growth of eutectic Si. At the same time, the refinement effect leads to a significant increase in the primary α-Al phase, which also inhibits the growth of eutectic Si. After adding 0.2wt.% of the refinement modifier of the present invention, the ultimate tensile strength, yield strength, elongation and microhardness of Al-7Si-0.3Mg alloy are increased from 165.96MPa, 69.89MPa, 5.07% and 62.5HV in the untreated state to 220.60MPa, 100.81MPa, 9.92% and 79.3HV, respectively, which are increased by 32.92%, 44.24%, 95.66% and 26.88%, respectively, and the mechanical properties of the alloy are significantly improved.

[0221] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A refining modifier, the phase composition includes α-Al, Al4 (Sr, La) and Ti2Al 20 La.

2. The refinement modifier according to claim 1, characterized in that: The chemical composition of the refining modifier includes, by mass percentage, 2.80-3.20% Ti, 4.25-4.45% La, 7.75-8.15% Sr, ≤0.20% Fe, ≤0.03% Mn, ≤0.50% Zn and the balance Al.

3. The method for preparing the refinement modifier according to claim 1 or 2, comprising the following steps: (1) mixing raw materials and performing melt reaction to obtain a melt; (2) Casting the melt obtained in step (1) to obtain a refined modifier.

4. The preparation method according to claim 3, characterized in that: The raw materials in step (1) include Al-Ti-La master alloy and Sr block.

5. The preparation method according to claim 3, characterized in that: In the step (1), the temperature of the melt reaction is 900-950° C., and the time of the melt reaction is 30-60 minutes.

6. The preparation method according to claim 3 or 5, characterized in that: The melt reaction in step (1) is carried out under stirring conditions.

7. The preparation method according to claim 3, characterized in that: The casting temperature in step (2) is 850-870°C.

8. Use of the refining modifier according to claim 1 or 2 or the refining modifier prepared by the preparation method according to any one of claims 3 to 7 in Al-Si-Mg alloy.

9. The use according to claim 8, characterized in that: The mass of the refining modifier is 0.1-0.5% of the mass of the Al-Si-Mg alloy.

10. The use according to claim 8, characterized in that: The method of application includes: The modified alloy is obtained by mixing an Al-Si-Mg alloy melt and a refining modifier and then casting.